RORγt-expressing dendritic cells are functionally versatile and evolutionarily conserved antigen-presenting cells - Hamsa Narasimhan; Maria L. Richter; Ramin Shakiba; Nikos E. Papaioannou; Christina Stehle; Kaushikk Ravi Rengarajan; Isabel Ulmert; Arek Kendirli; Clara de la Rosa; Pin-Yu Kuo; Abigail Altman; Philipp Münch; et al. (Proceedings of the National Academy of Sciences, 2025)
Conventional dendritic cells (cDCs) are potent antigen-presenting cells (APCs) that integrate signals from their environment allowing them to direct situation-adapted immunity. Thereby they harbor great potential for being targeted in vaccination, autoimmunity, and cancer. Here, we use fate mapping, functional analyses, and comparative cross-species transcriptomics to show that RORγt + DCs are a conserved, functionally versatile, and transcriptionally distinct type of DCs. RORγt + DCs entail various populations described in different contexts including Janus cells/RORγt-expressing extrathymic Aire-expressing cells (eTACs), subtypes of Thetis cells, RORγt + -DC (R-DC) like cells, cDC2C and ACY3 + DCs. We show that in response to inflammatory triggers, RORγt + DCs can migrate to lymph nodes and in the spleen can activate naïve CD4 + T cells. These findings expand the functional repertoire of RORγt + DCs beyond the known role of eTACs and Thetis cells in inducing T cell tolerance to self-antigens and intestinal microbes in mice. We further show that RORγt + DCs with proinflammatory features accumulate in autoimmune neuroinflammation in mice and men. Thus, our work establishes RORγt + DCs as immune sentinel cells that exhibit a broad functional spectrum ranging from inducing peripheral T cell tolerance to T cell activation depending on signals they integrate from their environment.